2010
DOI: 10.1111/j.1742-7843.2009.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kaempferol and Myricetin on Inducible Nitric Oxide Synthase Expression and Nitric Oxide Production in Rats

Abstract: When administered as drugs or consumed as food components, polyphenolic compounds synthesized in plants interfere with intracellular signal transduction pathways, including pathways of nitric oxide synthase expression. However, effects of these compounds in vivo do not always correlate with nitric oxide synthase-inhibiting activities revealed in experiments with cultured cells. The initial goal of this work was to compare effects of flavonoids kaempferol and myricetin on inducible nitric oxide synthase mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
4
8
0
Order By: Relevance
“…Anti-inflammatory activity of P. macrocarpa pericarp extract also proven through decreasing of iNOS expression in mice colon, this results in line with Rostoka et al [22] and Choi et al [23] whom study flavonoid isolates, state that kaempferol, myricetin and rutin lowering iNOS protein expression in the livers of mice, and myricetin lowering nitric oxide production in rat liver. Besides kaempferol, myricetin and rutin, naringin also can inhibit the activation of iNOS enzyme and activation of NF-κB through barriers to degrades IκB and translocation of p65, a subunit of the protein NF-κB which undergo translocation into the cell nucleus when NF-κB regardless of IκB [24].…”
Section: Discussionsupporting
confidence: 77%
“…Anti-inflammatory activity of P. macrocarpa pericarp extract also proven through decreasing of iNOS expression in mice colon, this results in line with Rostoka et al [22] and Choi et al [23] whom study flavonoid isolates, state that kaempferol, myricetin and rutin lowering iNOS protein expression in the livers of mice, and myricetin lowering nitric oxide production in rat liver. Besides kaempferol, myricetin and rutin, naringin also can inhibit the activation of iNOS enzyme and activation of NF-κB through barriers to degrades IκB and translocation of p65, a subunit of the protein NF-κB which undergo translocation into the cell nucleus when NF-κB regardless of IκB [24].…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, an in vivo study indicated that myricetin could attenuate the lipopolysaccharide-induced outburst of iNOS gene expression and decrease NO production in intact rat liver. 29 Our results also provided evidence that myricetin could reduce cytokine-induced NO formation. Thus, we conclude that myricetin might reduce NO production through the inhibition of NF-jB-dependent iNOS expression in this study.…”
supporting
confidence: 65%
“…The functions of NOS are summarized in Table 1. Decreased production of NO via suppressing or inhibiting NOS reduces arthritic symptoms and affords protection against the loss of body weight 17, 97. Anti-oxidants that are present in a number of plant extracts scavenge NO and other free radicals.…”
Section: Biochemical Mediators Of Inflammation and Arthritismentioning
confidence: 99%
“…The in vivo testing was performed using well-established experimental models of human RA (e.g., adjuvant-induced arthritis (AA) 47, collagen-induced arthritis (CIA) 8, 9 and streptococcal cell wall-induced arthritis 1012), whereas the in vitro testing was based on cultures of defined cell types (e.g., macrophages, chondrocytes and fibroblasts) 1316. For the in vivo studies, the plant products were tested either as an extract (e.g., water-extract and alcoholic extract) 5, 17–19 or as a purified bioactive compound (e.g., triptolide, curcumin, epigallocatechin-3-gallate (EGCG) and acetyl-11-keto-beta-boswellic acid (AKBA) 12, 13, 15, 20) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%